Determining Factors of Tourist Interest in Culinary Tourism in Malang - Saputri, Anggi; Hidayati, Laili; Sunaryo, Nonny Aji (E-Journal of Tourism, 2022)
Malang is one of the cities that is rich in tourism. Many types of tourism are available in Malang, such as nature tourism, religious tourism, artificial tourism, and culinary tourism. Culinary tourism is one type of tourism that has the potential to be developed. This can be seen from exploring the culinary arts in a tourist itinerary which is more desirable than visiting tourist attractions or just shopping. The exploration referred to here is that tourists prefer and even deliberately choose tourist destinations because they are interested in the culinary served. Currently the presence of culinary in Malang is very rapid. One of the culinary products that are very popular with tourists is meatballs. Bakso Kota Cak Man Is a legendary restaurant that provides meatballs. The significant increase in the number of culinary places makes culinary place owners obliged to think about strategies for how their business can survive. Therefore, there is a need for a study that can determine the determinants of tourist interest in culinary tourism in Malang. The purpose of this study was to determine the determinants of tourist interest in culinary tourism in Malang. This research method is a qualitative descriptive method to determine the determinants of tourist interest and to determine culinary tourism in the city of Malang. The results of the study indicate that there are several determinants of tourist interest in culinary tourism in the city of Malang, including tourists who are attracted to the city of Malang because of service, product quality, location and price. Keywords: Tourist Interest, Culinary Tourism, Malang